PHYSIOLOGICAL RESPONSE OF SOME TOMATO GENOTYPES (LYCOPERSICON ESCULENTUM L.) TO HIGH TEMPERATURE STRESS - Malgorzata BEROVA; Nevena STOEVA; Zlatko ZLATEV; Daniela GANEVA (Journal of Central European Agriculture, 2009)
Cultivated plants are often exposed to different types of environmental stress, which limits their development and productivity. High temperature stress induces considerable changes in the biochemistry and physiology of plants. The aim of the present investigation was to evaluate the physiological response of some tomato genotypes to a high temperature stress. Experiments were carried out during the stress period and after its elimination. Valuation of the tolerance of plants was carried out by means of a physiological test. It was observed that the high temperature stress has an inhibitory effect on the physiological state of tomato plants. The degree of its inhibited action was individual, depending on the genotype.